Edible film incorporated with chitosan and Artemisia annua oil nanoliposomes for inactivation of Escherichia coli O157:H7 on cherry tomato. (29th December 2016) - Cui, Haiying; Yuan, Lu; Li, Wei; Lin, Lin
Summary: As a natural antibacterial agent, Artemisia annua oil (AAO) exhibited significant antibacterial effect on Escherichia coli O157:H7. However, AAO was volatile and not suitable for surface coatings of fresh produce. Therefore, the edible agar films containing chitosan and AAO liposomes were engineered to overcome the defect. Chitosan was added in the film to enhance the antibacterial activity. Finally, the results showed the mean size of AAO liposomes was about 191.8 nm with a polydispersity index (PDI) of 0.463. The absolute zeta potential value was greater than 30 mV, and the loading efficiency (LE) of 5.0 mg mL −1 AAO liposome was 67.45%. As a proof of concept, the antibacterial activity of the films against E. coli O157:H7 on cherry tomatoes was evaluated. The results indicated that the incorporation of AAO liposomes as a natural antibacterial agent possessed bacteriostatic effect, which had potential for using the developed film as an active packaging. Abstract : The preparation of edible film for inactivation of Escherichia coli O157:H7 on cherry tomato.